Nonaqueous electrolyte and lithium secondary battery comprising same
By using a non-aqueous electrolyte containing a sulfonamide compound and lithium difluorophosphate in a lithium secondary battery to form a stable film, the problem of electrolyte side reaction of lithium secondary batteries at high temperatures is solved, and excellent storage characteristics and resistance characteristics are achieved.
Patent Information
- Application Number
- CN202380056652.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-12
- Filing Date
- 2023-08-10
- Publication Date
- 2025-03-14
AI Technical Summary
Lithium secondary batteries have electrolyte side reactions at high temperatures, resulting in increased resistance, reduced life and deterioration of storage performance.
The non-aqueous electrolyte containing a sulfonamide compound of a specific structural formula and lithium difluorophosphate is used to reduce side reactions of the electrolyte by forming a stable film on the electrode.
Achieve excellent storage characteristics and resistance characteristics of lithium secondary batteries at high temperatures, extending battery life and improving storage performance.
Smart Images

Figure BDA0005257990030000021 
Figure BDA0005257990030000041 
Figure BDA0005257990030000071
Abstract
Description
Technical Field
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims the benefit of Korean Patent Application No. 10-2022-0101642, filed on August 12, 2022, the disclosure of which is incorporated herein by reference in its entirety. Technical Field
[0004] The present invention relates to a non-aqueous electrolyte and a lithium secondary battery comprising the non-aqueous electrolyte. Background Art
[0005] In recent years, as the application fields of lithium secondary batteries have rapidly expanded not only to power supplies for electronic devices such as electricity, electronics, communications, and computers, but also to power storage supplies for large-area devices such as automobiles and power storage devices, the demand for secondary batteries with high capacity, high output, and high stability has been increasing.
[0006] In particular, as people pay attention to solving environmental problems and realizing a sustainable recycling society, research on power storage devices such as electric double layer capacitors and lithium-ion batteries is widely carried out. Among these battery technologies, lithium secondary batteries have attracted much attention as battery systems with the highest theoretical energy density.
[0007] Lithium secondary batteries are mainly composed of a positive electrode formed of a lithium-containing transition metal oxide, a negative electrode capable of storing lithium, an electrolyte as a medium for transmitting lithium ions, and a separator. Among them, since the electrolyte is known to be a component that greatly affects the stability and safety of the battery, a lot of research has been done on the electrolyte.
[0008] In this regard, a non-aqueous electrolyte containing a lithium salt, an organic solvent, etc. is generally used as the electrolyte of a lithium secondary battery, and a carbonate organic solvent, etc. is used as the organic solvent. In this case, for example, LiPF6 can be used as the lithium salt, and PF6 - In the case of anions, when the battery is exposed to high temperatures, it is very susceptible to heat, so there is a limitation in the generation of Lewis acids (such as HF or PF5) due to the thermal decomposition of lithium salts. The limitation is that Lewis acids (such as HF or PF5) will cause the organic solvent itself to decompose and destroy the solid electrolyte interface layer (SEI layer) formed on the surface of the negative electrode active material, thereby increasing the resistance of the lithium secondary battery, reducing the life span, and deteriorating the storage performance. Summary of the invention
[0009] Technical issues
[0010] One aspect of the present invention provides a nonaqueous electrolyte that can reduce side reactions of an electrolyte by forming a stable film on an electrode, thereby achieving excellent storage characteristics and resistance characteristics at high temperatures when applied to a lithium secondary battery.
[0011] Another aspect of the present invention provides a lithium secondary battery including the above-mentioned nonaqueous electrolyte.
[0012] Technical Solution
[0013] According to one aspect of the present invention, a non-aqueous electrolyte is provided, comprising: a lithium salt; an organic solvent; and an additive, wherein the additive comprises a first additive and a second additive, the first additive comprises a compound represented by the following Chemical Formula 1, and the second additive comprises lithium difluorophosphate.
[0014] [Chemical formula 1]
[0015]
[0016] In the above Chemical Formula 1, R1 is an alkoxy group having 1 to 10 carbon atoms substituted with at least one fluorine or an aryloxy group having 6 to 20 carbon atoms substituted with at least one fluorine, and R2 and R3 are each independently hydrogen, an alkyl group having 1 to 10 carbon atoms, or an aryl group having 6 to 20 carbon atoms.
[0017] In addition, according to another aspect of the present invention, there is provided a lithium secondary battery comprising: a positive electrode; a negative electrode facing the positive electrode; a separator disposed between the negative electrode and the positive electrode; and the above-mentioned nonaqueous electrolyte.
[0018] Beneficial Effects
[0019] The non-aqueous electrolyte of the present invention comprises a first additive comprising a sulfonamide compound having a specific structural formula and a second additive comprising lithium difluorophosphate as additives. The non-aqueous electrolyte of the present invention can reduce the side reaction of the electrolyte by forming a stable film on the electrode, and when applied to a lithium secondary battery, can achieve excellent storage characteristics and resistance characteristics at high temperatures. DETAILED DESCRIPTION
[0020] It should be understood that the terms or words used in this specification and claims should not be interpreted as being limited to the meanings defined in commonly used dictionaries, but should be interpreted as having meanings and concepts consistent with the technical ideas of the present invention based on the principle that the inventor can appropriately define terminological concepts to best interpret the present invention.
[0021] It should also be understood that the terms “comprises,” “comprising,” or “having” in this specification specify the presence of stated features, numbers, steps, elements, or a combination thereof, but do not exclude the presence or addition of one or more other features, numbers, steps, elements, or a combination thereof.
[0022] Meanwhile, before describing the present invention, unless otherwise specified in the present invention, the expression “*” represents a connecting portion (binding site) between the same atom or different atoms or chemical formula terminals.
[0023] In addition, "a" and "b" in the description of "a to b carbon atoms" in the specification each represent the number of carbon atoms contained in a specific functional group. That is, the functional group may include "a" to "b" carbon atoms. For example, "an alkyl group having 1 to 5 carbon atoms" refers to an alkyl group containing 1 to 5 carbon atoms, that is, CH3-, CH3CH2-, CH3CH2CH2-, (CH3)2CH-, CH3CH2CH2CH2-, (CH3)2CHCH2-, CH3CH2CH2CH2CH2-, (CH3)2CHCH2-, CH3CH2CH2CH2CH2-, (CH3)2CHCH2CH2-, etc.
[0024] In addition, in the present specification, alkyl or aryl may be substituted or unsubstituted. Unless otherwise defined, the term "substituted" means that at least one hydrogen bonded to carbon is replaced by an element other than hydrogen, for example, alkyl having 1 to 20 carbon atoms, alkenyl having 2 to 20 carbon atoms, alkynyl having 2 to 20 carbon atoms, alkoxy having 1 to 20 carbon atoms, cycloalkyl having 3 to 12 carbon atoms, cycloalkenyl having 3 to 12 carbon atoms, cycloalkynyl having 3 to 12 carbon atoms, heterocycloalkyl having 3 to 12 carbon atoms, heterocycloalkenyl having 3 to 12 carbon atoms, heterocycloalkynyl having 2 to 12 carbon atoms, aryloxy having 6 to 12 carbon atoms, halogen atoms, fluoroalkyl having 1 to 20 carbon atoms, nitro, aryl having 6 to 20 carbon atoms, heteroaryl having 2 to 20 carbon atoms, halogenated aryl having 6 to 20 carbon atoms, etc.
[0025] Hereinafter, the present invention will be described in more detail.
[0026] Non-aqueous electrolytes
[0027] The present invention relates to a non-aqueous electrolyte. More specifically, the non-aqueous electrolyte may be a non-aqueous electrolyte for a lithium secondary battery.
[0028] A nonaqueous electrolyte according to one aspect of the present invention comprises: a lithium salt; an organic solvent; and an additive, wherein the additive comprises a first additive and a second additive, the first additive comprises a compound represented by the following Chemical Formula 1, and the second additive comprises lithium difluorophosphate.
[0029] [Chemical formula 1]
[0030]
[0031] In the above Chemical Formula 1, R1 is an alkoxy group having 1 to 10 carbon atoms substituted with at least one fluorine or an aryloxy group having 6 to 20 carbon atoms substituted with at least one fluorine, and R2 and R3 are each independently hydrogen, an alkyl group having 1 to 10 carbon atoms, or an aryl group having 6 to 20 carbon atoms.
[0032] The non-aqueous electrolyte of the present invention includes a first additive including a sulfonamide compound having a specific structural formula and a second additive including lithium difluorophosphate as additives. The non-aqueous electrolyte of the present invention can reduce the side reaction of the electrolyte by forming a stable film on the electrode, and when applied to a lithium secondary battery, can achieve excellent storage characteristics and resistance characteristics at high temperatures.
[0033] (1) Lithium salt
[0034] As the lithium salt used in the present invention, various lithium salts commonly used in non-aqueous electrolytes for lithium secondary batteries can be used without limitation. For example, the lithium salt may include Li + as a cation, and may include at least one selected from the group consisting of: F - , Cl - Br - ,I - 、NO3 - 、N(CN)2 - 、BF4 - 、ClO4 - 、AlO4 - 、AlCl4 - PF6 - 、SbF6 - 、AsF6 - , B 10 Cl 10 - 、BF2C2O4 - , BC4O8 - PF4C2O4 - PF2C4O8 - 、(CF3)2PF4 - 、(CF3)3PF3 - 、(CF3)4PF2 - 、(CF3)5PF - 、(CF3)6P - CF3SO3 - 、C4F9SO3 - CF3CF2SO3- 、(FSO2)2N - CF3CF2(CF3)2CO - 、(CF3SO2)2CH - 、CH3SO3 - CF3(CF2)7SO3 - CF3CO2 - 、CH3CO2 - 、SCN - and (CF3CF2SO2)2N - .
[0035] Specifically, the lithium salt may include at least one selected from the group consisting of LiCl, LiBr, LiI, LiBF4, LiClO4, LiAlO4, LiAlCl4, LiPF6, LiSbF6, LiAsF6, LiB 10 Cl 10 , LiB(C2O4)2(LiBOB), LiCF3SO3, LiN(SO2F)2(LiFSI), LiCH3SO3, LiCF3CO2, LiCH3CO2 and LiN(SO2CF2CF3)2(LiBETI). Specifically, the lithium salt may include at least one selected from the group consisting of LiBF4, LiClO4, LiPF6, LiB(C2O4)2(LiBOB), LiCF3SO3, LiN(SO2CF3)2(LiFSI), (LiN(SO2F)2(LiFSI) and LiN(SO2CF2CF3)2(LiBETI).
[0036] The concentration of the lithium salt contained in the non-aqueous electrolyte may be 0.5 M to 5 M, specifically 0.8 M to 4 M, and more specifically 0.8 M to 2.0 M. When the concentration of the lithium salt satisfies the above range, the lithium ion yield (Li + migration number) and the degree of dissociation of lithium ions, thereby improving the output characteristics of the battery.
[0037] (2) Organic solvents
[0038] The organic solvent is a non-aqueous solvent commonly used in lithium secondary batteries, and is not particularly limited as long as it can minimize decomposition caused by oxidation reaction and the like during charge and discharge of the secondary battery.
[0039] Specifically, the organic solvent includes at least one selected from the group consisting of a cyclic carbonate-based organic solvent, a linear carbonate-based organic solvent, a linear ester-based organic solvent, and a cyclic ester-based organic solvent.
[0040] Specifically, the organic solvent may include a cyclic carbonate-based organic solvent, a linear carbonate-based organic solvent, or a mixture thereof.
[0041] The cyclic carbonate organic solvent is an organic solvent that is a high-viscosity organic solvent and can well dissociate the lithium salt in the electrolyte due to its high dielectric constant. Specifically, it can include at least one organic solvent selected from the group consisting of ethylene carbonate (EC), propylene carbonate (PC), 1,2-butylene carbonate, 2,3-butylene carbonate, 1,2-pentylene carbonate, 2,3-pentylene carbonate, and vinylene carbonate, and more specifically, it can include ethylene carbonate.
[0042] In addition, the straight-chain carbonate solvent is an organic solvent with low viscosity and low dielectric constant, and specifically, may include at least one selected from the group consisting of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate, ethyl methyl carbonate (EMC), methyl propyl carbonate and ethyl propyl carbonate, and more specifically, may include ethyl methyl carbonate (EMC).
[0043] The organic solvent may be a mixture of a cyclic carbonate organic solvent and a linear carbonate organic solvent. In this case, the cyclic carbonate organic solvent and the linear carbonate organic solvent may be mixed in a volume ratio of 10:90 to 40:60, specifically, in a volume ratio of 10:90 to 30:70, more specifically, in a volume ratio of 15:85 to 30:70. When the mixing ratio of the cyclic carbonate organic solvent and the linear carbonate organic solvent satisfies the above range, high dielectric constant and low viscosity characteristics may be satisfied simultaneously, and excellent ion conductivity characteristics may be achieved.
[0044] In addition, in order to prepare an electrolyte with high ion conductivity, in addition to at least one carbonate organic solvent selected from the group consisting of cyclic carbonate organic solvents and linear carbonate organic solvents, the organic solvent may further include at least one ester organic solvent selected from the group consisting of linear ester organic solvents and cyclic ester organic solvents.
[0045] The linear ester-based organic solvent may include at least one organic solvent selected from the group consisting of methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, and butyl propionate.
[0046] In addition, the cyclic ester organic solvent may specifically include at least one selected from the group consisting of γ-butyrolactone, γ-valerolactone, γ-caprolactone, σ-valerolactone, and ε-caprolactone.
[0047] Meanwhile, if necessary, any organic solvent commonly used in non-aqueous electrolytes may be used as the organic solvent without limitation. For example, at least one organic solvent selected from ether organic solvents, glycol ether organic solvents, and nitrile organic solvents may be included.
[0048] As the ether solvent, any one selected from the group consisting of dimethyl ether, diethyl ether, dipropyl ether, methyl ethyl ether, methyl propyl ether, ethyl propyl ether, 1,3-dioxolane (DOL) and 2,2-bis(trifluoromethyl)-1,3-dioxolane (TFDOL) or a mixture of two or more thereof may be used, but the ether solvent is not limited thereto.
[0049] Glycol ether solvents are solvents having a higher dielectric constant and a lower surface tension than straight-chain carbonate organic solvents and having lower reactivity with metals, and may include at least one selected from the group consisting of dimethoxyethane (glycol dimethyl ether, DME), diethoxyethane, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether and tetraethylene glycol dimethyl ether (TEGDME), but glycol ether solvents are not limited thereto.
[0050] The nitrile organic solvent may include at least one selected from the group consisting of acetonitrile, propionitrile, butyronitrile, valeronitrile, octanonitrile, heptanenitrile, cyclopentanenitrile, cyclohexanenitrile, 2-fluorobenzonitrile, 4-fluorobenzonitrile, difluorobenzonitrile, trifluorobenzonitrile, benzyl cyanide, 2-fluorobenzene acetonitrile and 4-fluorobenzene acetonitrile, but the nitrile organic solvent is not limited thereto.
[0051] (3) Additives
[0052] The non-aqueous electrolyte of the present invention contains additives. The additives include a first additive and a second additive. The first additive includes a compound represented by Chemical Formula 1. The second additive includes lithium difluorophosphate (LiDFP).
[0053] In the present invention, the second additive includes lithium difluorophosphate, which can react with an organic solvent (e.g., ethylene carbonate) to form a SEI film containing an organic component on the negative electrode, but there is a limitation that when only lithium difluorophosphate is used as an additive, the inorganic component (e.g., LiF, etc.) in the SEI film is insufficient, so that the lithium difluorophosphate is first decomposed at the positive electrode, and the SEI film of the negative electrode is not fully formed. At the same time, the compound represented by the above chemical formula 1 contained in the first additive is a sulfonamide compound substituted with an alkoxy or aryloxy group substituted with at least one fluorine, and the alkoxy or aryloxy group substituted with at least one fluorine is a relatively weak electron-withdrawing group compared with F-, CF3-, etc., so the compound may be easily reduced at the negative electrode, thereby easily forming a film containing an inorganic component (e.g., LiF). Therefore, since the non-aqueous electrolyte of the present invention using the first additive and the second additive at the same time can form a SEI film containing all organic / inorganic components on the negative electrode, the non-aqueous electrolyte can have excellent effects of preventing side reactions of the electrolyte and inhibiting gas generation, and can improve the storage characteristics and resistance characteristics of the lithium secondary battery at high temperature to an excellent level.
[0054] In addition, the non-aqueous electrolyte of the present invention using both the first additive and the second additive can form an SEI film in the form of an inorganic component such as LiF distributed in the SEI film containing an organic component having flexibility, so that an SEI film having improved flexibility and durability can be formed on the electrode, thereby improving the overall performance of the lithium secondary battery such as the high temperature performance to an excellent level. If only the first additive is included as an additive in the non-aqueous electrolyte, or only the second additive is included in the non-aqueous electrolyte, the durability or flexibility will be reduced, thereby failing to achieve the effect of improving the high temperature performance required for the lithium secondary battery of the present invention.
[0055] The first additive includes a compound represented by the following Chemical Formula 1:
[0056] [Chemical formula 1]
[0057]
[0058] In the above Chemical Formula 1, R1 is an alkoxy group having 1 to 10 carbon atoms substituted with at least one fluorine or an aryloxy group having 6 to 20 carbon atoms substituted with at least one fluorine, and R2 and R3 are each independently hydrogen, an alkyl group having 1 to 10 carbon atoms, or an aryl group having 6 to 20 carbon atoms.
[0059] R1 can be an alkoxy group having 1 to 10 carbon atoms substituted with at least one fluorine or an aryloxy group having 6 to 20 carbon atoms substituted with at least one fluorine, specifically an alkoxy group having 1 to 10 carbon atoms substituted with at least one fluorine, more specifically an alkoxy group having 1 to 5 carbon atoms substituted with at least one fluorine, and even more specifically CF3O-, CF3CF2O- or CF3CH2O-, and from the perspective of easily forming a negative electrode SEI film, even more specifically CF3CH2O-.
[0060] R2 and R3 can each independently be hydrogen, an alkyl group having 1 to 10 carbon atoms or an aryl group having 6 to 20 carbon atoms, specifically hydrogen, an alkyl group having 1 to 5 carbon atoms, more specifically an alkyl group having 1 to 5 carbon atoms, and even more specifically a methyl group from the perspective of promoting a stable reaction during SEI film formation.
[0061] Specifically, the compound represented by the above chemical formula 1 may include at least one selected from the group consisting of a compound represented by the following chemical formula 2, a compound represented by the following chemical formula 3, and a compound represented by the following chemical formula 4. From the perspective of being able to easily form a SEI film containing inorganic components such as LiF on the negative electrode, it is specifically a compound represented by the following chemical formula 2.
[0062] [Chemical formula 2]
[0063]
[0064] [Chemical formula 3]
[0065]
[0066] [Chemical formula 4]
[0067]
[0068] The content of the first additive in the non-aqueous electrolyte may be 0.01 wt % to 10 wt %, specifically 0.1 wt % to 2 wt %, more specifically 0.2 wt % to 1 wt %, more specifically 0.5 wt % to 1 wt %, and even more specifically 0.7 wt % to 1 wt %. If the content of the compound represented by the above chemical formula 1 satisfies the above range, it is preferred in terms of sufficiently imparting durability to the SEI film and preventing the increase in resistance of the lithium secondary battery due to excessive addition and the resulting decrease in life performance.
[0069] Meanwhile, the second additive includes lithium difluorophosphate, which can react with an organic solvent (eg, ethylene carbonate) to form a SEI film containing an organic component on the negative electrode.
[0070] The content of the second additive in the non-aqueous electrolyte may be 0.01 wt % to 10 wt %, specifically 0.1 wt % to 2 wt %, more specifically 0.2 wt % to 1 wt %, and even more specifically 0.8 wt % to 1 wt %. If the content of the second additive satisfies the above range, it is preferred in terms of fully giving the SEI film flexibility, being beneficial to improving resistance characteristics, and preventing the increase in resistance of the lithium secondary battery due to excessive addition and the resulting decrease in life performance.
[0071] The weight ratio of the first additive to the second additive can be 10:90 to 90:10, specifically 20:80 to 80:20, more specifically 32:68 to 70:30, even more specifically 35:65 to 60:40, even more specifically 53:47 to 60:40, at the above weight ratio, the flexibility and durability of the SEI film can be improved to a preferred level at the same time.
[0072] In addition to the first additive and the second additive, the additive may further include an additional additive. The additional additive may be included in the non-aqueous electrolyte to prevent the non-aqueous electrolyte from decomposing in a high output environment to cause the negative electrode to collapse, or to achieve low temperature high rate discharge characteristics, high temperature stability, overcharge prevention, and battery expansion suppression effects at high temperatures.
[0073] Specifically, the additional additive can be at least one selected from the group consisting of vinylene carbonate, vinyl ethylene carbonate, fluoroethylene carbonate, propane sultone, propylene sultone, succinonitrile, adiponitrile, ethylene sulfate, lithium difluorooxalatoborate (LiODFB), lithium dioxalatoborate (LiBOB), 3-trimethoxysilyl-propyl-N-aniline (TMSPa), and tris(triethylsilyl) phosphite (TMSPi), specifically vinylene carbonate.
[0074] The content of the additional additive in the non-aqueous electrolyte may be 0.1 wt % to 15 wt %.
[0075] Lithium secondary battery
[0076] In addition, the present invention also provides a lithium secondary battery comprising the non-aqueous electrolyte.
[0077] Specifically, the lithium secondary battery may include: a positive electrode; a negative electrode facing the positive electrode; a separator provided between the negative electrode and the positive electrode; and the above-mentioned nonaqueous electrolyte.
[0078] In this case, the lithium secondary battery of the present invention can be prepared according to conventional methods known in the art. For example, after forming an electrode assembly by sequentially stacking a positive electrode, a negative electrode, and a separator disposed between the positive electrode and the negative electrode, the lithium secondary battery of the present invention can be prepared by inserting the electrode assembly into a battery case and injecting the non-aqueous electrolyte of the present invention.
[0079] (1) Positive electrode
[0080] The positive electrode may include: a positive electrode current collector; and a positive electrode active material layer provided on at least one surface of the positive electrode current collector.
[0081] The positive electrode current collector is not particularly limited as long as it has high conductivity and does not cause adverse chemical changes in the battery. Specifically, the positive electrode current collector may include at least one selected from the group consisting of copper, stainless steel, aluminum, nickel, titanium, fired carbon, and aluminum cadmium alloy, and preferably aluminum.
[0082] The thickness of the positive electrode current collector is generally 3 μm to 500 μm.
[0083] The positive electrode current collector may have fine irregularities formed on its surface to enhance the adhesion of the positive electrode active material. For example, the positive electrode current collector may be used in various shapes: for example, a film, a sheet, a foil, a net, a porous body, a foam body, and a non-woven fabric body, etc.
[0084] The positive electrode active material layer is provided on at least one surface of the positive electrode current collector. Specifically, the positive electrode active material layer may be provided on one surface or both surfaces of the positive electrode current collector.
[0085] The positive electrode active material layer may include a positive electrode active material.
[0086] The positive electrode active material is a compound capable of reversibly inserting and extracting lithium. Specifically, it may include a lithium transition metal composite oxide containing lithium and at least one transition metal selected from nickel, cobalt, manganese, and aluminum. Preferably, it may include a lithium transition metal composite oxide containing lithium and a transition metal including nickel, cobalt, and manganese.
[0087] For example, the lithium transition metal composite oxide may include lithium manganese-based oxides (e.g., LiMnO2, LiMn2O4, etc.), lithium cobalt-based oxides (e.g., LiCoO2, etc.), lithium nickel-based oxides (e.g., LiNiO2, etc.), lithium nickel manganese-based oxides (e.g., LiNi 1-Y Mn Y O2 (where 0 < Y < 1), LiMn 2-z Ni z O4 (where 0 < Z < 2), etc.), lithium nickel cobalt-based oxides (e.g., LiNi 1- Y1 Co Y1O2 (where 0 < Y1 < 1, etc.), lithium manganese cobalt oxides (e.g., LiCo 1-Y2 Mn Y2 O2 (where 0 < Y2 < 1), LiMn 2- z1 Co z1 O4 (where 0 < Z1 < 2, etc.), lithium nickel manganese cobalt oxides (e.g., Li(Ni p Co q Mn r1 )O2 (where 0 < p < 1, 0 < q < 1, 0 < r1 < 1, p + q + r1 = 1) or Li(Ni p1 Co q1 Mn r2 )O4 (where 0 < p1 < 2, 0 < q1 < 2, 0 < r2 < 2, p1 + q1 + r2 = 2, etc.), or lithium nickel cobalt transition metal (M) oxides (e.g., Li(Ni p2 Co q2 Mn r3 M S2 )O2 (where M is selected from the group consisting of aluminum (Al), iron (Fe), vanadium (V), chromium (Cr), titanium (Ti), tantalum (Ta), magnesium (Mg), and molybdenum (Mo), and p2, q2, r3, and s2 are each independently the atomic fraction of the element, where 0 < p2 < 1, 0 < q2 < 1, 0 < r3 < 1, 0 < S2 < 1, p2 + q2 + r3 + S2 = 1), etc.), and may include any one or two or more of these compounds. Among these materials, in terms of improving the capacity characteristics and stability of the battery, the lithium transition metal composite oxide may include LiCoO2, LiMnO2, LiNiO2, lithium nickel manganese cobalt oxides (e.g., Li(Ni 0.6 Mn 0.2 Co 0.2 )O2, Li(Ni 0.5 Mn 0.3 Co 0.2 )O2, Li(Ni 0.7 Mn 0.15 Co 0.15 )O2 or Li(Ni 0.8 Mn 0.1 Co 0.1 )O2), or lithium nickel cobalt aluminum oxides (e.g., Li(Ni 0.8 Co 0.15 Al 0.05 )O2, etc.). Considering the significant improvement effect brought by controlling the type and content ratio of the components constituting the lithium transition metal composite oxide, the lithium transition metal composite oxide may be Li(Ni 0.6 Mn 0.2 Co 0.2 )O2, Li(Ni0.5 Mn 0.3 Co 0.2 )O2、Li(Ni 0.7 Mn 0.15 Co 0.15 )O2 or Li(Ni 0.8 Mn 0.1 Co 0.1 )O2, etc., and any one or a mixture of two or more thereof can be used.
[0088] More specifically, the positive electrode active material may be a lithium transition metal composite oxide, and may contain nickel of 60 mol% or more based on the total molar number of transition metals contained in the lithium transition metal composite oxide. Specifically, the positive electrode active material may be a lithium transition metal composite oxide, and the transition metal may include: nickel; and at least one selected from manganese, cobalt and aluminum, and the content of nickel may be 60 mol% or more, specifically 60 mol% to 90 mol%, based on the total molar number of transition metals. When the above-mentioned non-aqueous electrolyte is used together with a lithium transition metal composite oxide using a high content of nickel, it is preferred in terms of reducing byproducts on the gas generated by structural collapse.
[0089] In addition, the positive electrode active material may further include a lithium composite transition metal oxide represented by the following Chemical Formula 5:
[0090] [Chemical formula 5]
[0091] Li 1+x (Ni a Co b Mn c M d )O2
[0092] In the above chemical formula 5, M is one selected from W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B and Mo, 1+x, a, b, c and d are each independently the atomic fraction of the element, wherein 0≤x≤0.2, 0.50≤a<1, 0 <b≤0.25,0<c≤0.25,0≤d≤0.1,a+b+c+d=1。
[0093] Preferably, the above-mentioned a, b, c and d may be 0.70≤a≤0.95, 0.025≤b≤0.20, 0.025≤c≤0.20, and 0≤d≤0.05, respectively.
[0094] In addition, the above-mentioned a, b, c and d may be 0.80≤a≤0.95, 0.025≤b≤0.15, 0.025≤c≤0.15, and 0≤d≤0.05, respectively.
[0095] Furthermore, the above-mentioned a, b, c and d may be 0.85≤a≤0.90, 0.05≤b≤0.10, 0.05≤c≤0.10, and 0≤d≤0.03, respectively.
[0096] In consideration of showing sufficient capacity of the positive electrode active material, the positive electrode active material content in the positive electrode active material layer may be 80 wt % to 99 wt %, preferably 92 wt % to 98.5 wt %.
[0097] The positive electrode active material layer may further include a conductive agent and / or a binder together with the above-mentioned positive electrode active material.
[0098] The binder is a component that facilitates bonding between the active material and the conductive agent and to the current collector, and specifically may include at least one selected from the group consisting of polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene rubber (EPDM), sulfonated EPDM, styrene butadiene rubber and fluororubber, preferably including polyvinylidene fluoride.
[0099] In terms of ensuring sufficient bonding force between components such as the positive electrode active material, the binder content in the positive electrode active material layer may be 1 wt % to 20 wt %, preferably 1.2 wt % to 10 wt %.
[0100] The conductive agent is not particularly limited as long as it can be used to assist and improve the conductivity of the secondary battery and has conductivity without causing adverse chemical changes. Specifically, the positive electrode conductive agent may include at least one selected from the group consisting of the following materials: graphite, such as natural graphite or artificial graphite; carbon black, such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black or thermal black; conductive fibers, such as carbon fibers or metal fibers; conductive tubes, such as carbon nanotubes; fluorocarbons; metal powders, such as aluminum powder or nickel powder; conductive whiskers, such as zinc oxide whiskers or potassium titanate whiskers; conductive metal oxides, such as titanium oxide; and polyphenylene derivatives, preferably including carbon black in terms of improving conductivity.
[0101] In terms of ensuring sufficient conductivity, the content of the conductive agent in the positive electrode active material layer may be 1 wt % to 20 wt %, preferably 1.2 wt % to 10 wt %.
[0102] The thickness of the positive electrode active material layer may be 30 μm to 400 μm, preferably 40 μm to 110 μm.
[0103] The positive electrode may be prepared by coating a positive current collector with a positive electrode slurry containing a positive electrode active material and optionally a binder, a conductive agent, and a solvent for forming the positive electrode slurry, and then drying and calendering the coated positive electrode current collector.
[0104] The solvent used to form the positive electrode slurry may include an organic solvent, such as N-methyl-2-pyrrolidone (NMP). The solid content in the positive electrode slurry may be 40 wt % to 90 wt %, in particular 50 wt % to 80 wt %.
[0105] (2) Negative electrode
[0106] Negative side facing positive side.
[0107] The negative electrode may include a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector.
[0108] The negative electrode current collector is not particularly limited as long as it has high conductivity and does not cause adverse chemical changes in the battery. Specifically, copper, stainless steel, aluminum, nickel, titanium, fired carbon, copper or stainless steel surface-treated with one of carbon, nickel, titanium or silver, or aluminum-cadmium alloys can be used as the negative electrode current collector.
[0109] The thickness of the negative electrode current collector may generally be 3 μm to 500 μm.
[0110] The negative electrode current collector may have fine concavoconvexities formed on its surface to enhance the adhesion of the negative electrode active material. For example, the negative electrode current collector may be used in various shapes such as films, sheets, foils, nets, porous bodies, foams, and nonwoven fabrics.
[0111] The negative electrode active material layer is disposed on at least one surface of the negative electrode current collector. Specifically, the negative electrode active material layer may be disposed on one surface or both surfaces of the negative electrode current collector.
[0112] The negative electrode active material layer may include a negative electrode active material.
[0113] The negative electrode active material is a material that can reversibly insert / deinsert lithium ions, and may include at least one selected from the group consisting of carbon-based active materials, (quasi)metallic active materials, and lithium metal, and specifically, may include at least one selected from the group consisting of carbon-based active materials and (quasi)metallic active materials. Alternatively, the negative electrode active material may include a carbon-based active material and a (quasi)metallic active material.
[0114] The carbon-based active material may include at least one selected from the group consisting of artificial graphite, hard carbon, soft carbon, carbon black, graphene, and fibrous carbon, and may preferably include graphite.
[0115] The average particle size (D 50 ) can be 10 μm to 30 μm, preferably 15 μm to 25 μm.
[0116] Specifically, the (quasi)metallic active materials may include: at least one (quasi)metal selected from the group consisting of Cu, Ni, Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al, V, Ti and Sn; an alloy of lithium and at least one (quasi)metal selected from the group consisting of Cu, Ni, Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al, V, Ti and Sn; an oxide of at least one (quasi)metal selected from the group consisting of Cu, Ni, Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al, V, Ti and Sn; lithium titanium oxide (LTO); lithium vanadium oxide, etc.
[0117] More specifically, the (quasi)metal-based active material may include a silicon-based active material.
[0118] The silicon-based active material may include SiO x (0≤x<2). Since SiO2 does not react with lithium ions and therefore cannot store lithium, x is preferably within the above range, and more preferably, the silicon-based active material may be SiO.
[0119] In terms of reducing side reactions with the electrolyte while maintaining structural stability during charge and discharge, the average particle size (D 50 ) can be 1 μm to 30 μm, preferably 2 μm to 15 μm.
[0120] The content of the negative electrode active material in the negative electrode active material layer may be 60 wt % to 99 wt %, preferably 75 wt % to 98 wt %.
[0121] The negative electrode active material layer may further contain a conductive agent and / or a binder together with the negative electrode active material.
[0122] The binder can be used to improve the adhesion between the negative electrode active material layer and the negative electrode current collector and improve the battery performance. It can include, for example, at least one selected from the group consisting of polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride (PVDF), polyacrylonitrile, polymethyl methacrylate, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, polyacrylic acid, ethylene propylene diene rubber (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber and materials in which hydrogen is replaced by Li, Na or Ca, etc., and can also include various copolymers thereof.
[0123] The binder content in the negative electrode active material layer may be 0.5 wt % to 10 wt %.
[0124] There is no particular limitation on the conductive agent as long as it has conductivity and does not cause adverse chemical changes in the battery, and the following conductive materials can be used: for example, graphite, such as natural graphite or artificial graphite; carbon black, such as acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black; conductive fibers, such as carbon fibers or metal fibers; conductive tubes, such as carbon nanotubes; fluorocarbons; metal powders, such as aluminum powder and nickel powder; conductive whiskers, such as zinc oxide whiskers and potassium titanate whiskers; conductive metal oxides, such as titanium oxide; or polyphenylene derivatives.
[0125] The content of the conductive agent in the negative electrode active material layer may be 0.5 wt % to 10 wt %, preferably 1 wt % to 5 wt %.
[0126] The thickness of the negative electrode active material layer may be 10 μm to 100 μm, preferably 50 μm to 80 μm.
[0127] The negative electrode may be prepared by coating at least one surface of a negative electrode collector with a negative electrode slurry including a negative electrode active material, a binder, a conductive agent, and a solvent for forming the negative electrode slurry, and then drying and rolling the coated negative electrode collector.
[0128] For example, the solvent for forming the negative electrode slurry may include, for example, at least one selected from the group consisting of distilled water, N-methyl-2-pyrrolidone (NMP), ethanol, methanol and isopropanol, preferably distilled water in terms of promoting the dispersion of the negative electrode active material, binder and / or conductive agent. The solid content in the negative electrode slurry may be 30 wt % to 80 wt %, particularly 40 wt % to 70 wt %.
[0129] (3) Diaphragm
[0130] In addition, conventional porous polymer films used as conventional diaphragms can be used alone or in layers as diaphragms, for example, porous polymer films prepared by polyolefin polymers (e.g., ethylene homopolymers, propylene homopolymers, ethylene / butene copolymers, ethylene / hexene copolymers, and ethylene / methacrylate copolymers). In addition, conventional porous nonwoven fabrics can be used, such as nonwoven fabrics formed by high melting point glass fibers or polyethylene terephthalate fibers, but the present invention is not limited thereto. In addition, a coated diaphragm including a ceramic component or a polymer material can be used to ensure heat resistance or mechanical strength, and a diaphragm with a monolayer or multilayer structure can be optionally used.
[0131] The shape of the lithium secondary battery of the present invention is not particularly limited, but a cylindrical type using a can, a prismatic type, a pouch type, or a coin type may be used.
[0132] Hereinafter, the present invention will be described in more detail with reference to specific embodiments. However, the following embodiments are only used to illustrate the present invention, and the scope of the present invention is not limited thereto. It is obvious to those skilled in the art that various modifications and changes can be made within the scope and technical spirit of the present invention. These modifications and changes all fall within the scope of the claims contained herein.
[0133] Examples and Comparative Examples
[0134] Example 1
[0135] (Preparation of non-aqueous electrolyte)
[0136] As the organic solvent, a mixture of ethylene carbonate (EC) and ethyl methyl carbonate (EMC) in a volume ratio of 30:70 was used.
[0137] LiPF6 as a lithium salt, a compound represented by the following Chemical Formula 2 as a first additive, lithium difluorophosphate as a second additive, and vinylene carbonate (VC) as an additional additive were added to an organic solvent to prepare a nonaqueous electrolyte.
[0138] The concentration of LiPF6 in the non-aqueous electrolyte was 1.2M.
[0139] The content of the compound represented by the above Chemical Formula 2 in the non-aqueous electrolyte was 0.5 wt %, the content of lithium difluorophosphate in the non-aqueous electrolyte was 0.8 wt %, and the content of vinylene carbonate in the non-aqueous electrolyte was 0.5 wt %.
[0140] [Chemical formula 2]
[0141]
[0142] (Manufacturing of lithium secondary batteries)
[0143] The positive electrode active material (LiNi 0.90 Co 0.06 Mn 0.03 Al 0.01 O2), a conductive agent (carbon black) and a binder (polyvinylidene fluoride) were added to N-methyl-2-pyrrolidone (NMP) as a solvent in a weight ratio of 97.6:0.8:1.6 to prepare a positive electrode material mixture slurry (solid content: 60 wt%). The positive electrode material mixture slurry was coated on one surface of a positive electrode current collector (aluminum film) with a thickness of 13.5 μm, dried and rolled to prepare a positive electrode.
[0144] The negative electrode active material (a mixture of graphite and SiO2 in a weight ratio of 90:10), a conductive agent (carbon black) and a binder (styrene-butadiene rubber / carboxymethyl cellulose) were added to distilled water as a solvent in a weight ratio of 97.6:1.6:0.8 to prepare a negative electrode material mixture slurry (solid content: 60 wt%). The negative electrode material mixture slurry was coated on one surface of a negative electrode current collector (copper film) having a thickness of 6 μm, dried and rolled to prepare a negative electrode.
[0145] In a dry room, a polyethylene porous film separator was inserted between the positive electrode and the negative electrode prepared above, and then the prepared nonaqueous electrolyte was injected therein to manufacture a lithium secondary battery.
[0146] Example 2
[0147] A nonaqueous electrolyte and a lithium secondary battery were prepared in the same manner as in Example 1, except that 0.1 wt % instead of 0.5 wt % of the compound represented by the above Chemical Formula 2 was added as the first additive to the nonaqueous electrolyte.
[0148] Example 3
[0149] A nonaqueous electrolyte and a lithium secondary battery were prepared in the same manner as in Example 1, except that 1 wt % instead of 0.5 wt % of the compound represented by the above Chemical Formula 2 was added as the first additive to the nonaqueous electrolyte.
[0150] Example 4
[0151] A nonaqueous electrolyte and a lithium secondary battery were prepared in the same manner as in Example 1, except that 0.5 wt % instead of 0.8 wt % of lithium difluorophosphate was added as the second additive to the nonaqueous electrolyte.
[0152] Example 5
[0153] A nonaqueous electrolyte and a lithium secondary battery were prepared in the same manner as in Example 1, except that 1 wt % instead of 0.8 wt % of lithium difluorophosphate was added as the second additive to the nonaqueous electrolyte.
[0154] Comparative Example 1
[0155] A nonaqueous electrolyte and a lithium secondary battery were prepared in the same manner as in Example 1, except that the first additive was not added.
[0156] Comparative Example 2
[0157] A nonaqueous electrolyte and a lithium secondary battery were prepared in the same manner as in Example 1, except that the first additive and the second additive were not added.
[0158] Comparative Example 3
[0159] A nonaqueous electrolyte and a lithium secondary battery were prepared in the same manner as in Example 1, except that the second additive was not added and 0.5 wt % of the compound represented by the following Chemical Formula 6 was added to the nonaqueous electrolyte instead of the compound represented by the above Chemical Formula 2 as the first additive.
[0160] [Chemical formula 6]
[0161]
[0162] Comparative Example 4
[0163] A nonaqueous electrolyte and a lithium secondary battery were prepared in the same manner as in Example 1 except that the second additive was not added.
[0164] Experimental example
[0165] Experimental Example 1: Evaluation of capacity retention after high temperature storage
[0166] After the lithium secondary batteries manufactured in the above-mentioned embodiments and comparative examples were subjected to a formation process, each lithium secondary battery was charged to 4.2V (0.05C cutoff) at a rate of 0.33C under constant current / constant voltage (CC / CV) conditions at 25°C, and then discharged to 2.80V at a rate of 0.33C under constant current (CC) conditions to measure the initial discharge capacity.
[0167] Then, the lithium secondary battery was fully charged to 100% SOC under charging conditions and stored at high temperature (60°C) for 8 weeks. Then, the battery was transferred to a charger and discharger at room temperature (25°C), and then discharged under discharge conditions to measure the discharge capacity, and the capacity retention rate was calculated by the following mathematical formula, and the results are shown in Table 1 below.
[0168] Capacity retention rate (%) = (discharge capacity after high temperature storage / initial discharge capacity) × 100
[0169] Experimental Example 2: Evaluation of resistance increase rate after high temperature storage
[0170] After the lithium secondary batteries manufactured in the above-mentioned embodiments and comparative examples were subjected to a formation process, each lithium secondary battery was charged to 4.2 V (0.05 C cut-off) at a rate of 0.33 C under constant current / constant voltage (CC / CV) conditions at 25° C., and then discharged to 2.80 V at a rate of 0.33 C under constant current (CC) conditions to measure the initial resistance.
[0171] Then, the lithium secondary battery was fully charged to 100% SOC under charging conditions and stored at high temperature (60°C) for 8 weeks. Then, the battery was transferred to a charger and discharger at room temperature (25°C), and then the resistance was measured, and the resistance increase rate was calculated by the following mathematical formula, and the results are shown in Table 1 below.
[0172] Resistance increase rate (%) = {(resistance after high temperature storage - initial resistance) / (initial resistance)} × 100
[0173] [Table 1]
[0174]
[0175] Referring to Table 1, it can be confirmed that the lithium secondary batteries of Examples 1 to 5 using the nonaqueous electrolyte containing the first and second additives of the present invention have excellent high temperature storage life performance and lower resistance increase rate compared to the lithium secondary batteries of Comparative Examples 1 to 4.
Claims
1. A non-aqueous electrolyte comprising: Lithium salts; organic solvents; and additive, in, The additive includes a first additive and a second additive, the first additive includes a compound represented by the following chemical formula 1, and the second additive includes lithium difluorophosphate: [Chemical formula 1] In the above Chemical Formula 1, R1 is an alkoxy group having 1 to 10 carbon atoms substituted with at least one fluorine group or an aryloxy group having 6 to 20 carbon atoms substituted with at least one fluorine group, and R2 and R3 are each independently hydrogen, an alkyl group having 1 to 10 carbon atoms, or an aryl group having 6 to 20 carbon atoms.
2. The nonaqueous electrolyte according to claim 1, wherein The compound represented by Chemical Formula 1 includes at least one selected from the group consisting of a compound represented by the following Chemical Formula 2, a compound represented by the following Chemical Formula 3, and a compound represented by the following Chemical Formula 4: [Chemical formula 2] [Chemical formula 3] [Chemical formula 4] 3. The nonaqueous electrolyte according to claim 1, wherein The content of the first additive in the non-aqueous electrolyte is 0.1 wt % to 10 wt %.
4. The nonaqueous electrolyte according to claim 1, wherein The content of the second additive in the non-aqueous electrolyte is 0.1 wt % to 10 wt %.
5. The nonaqueous electrolyte according to claim 1, wherein The weight ratio of the first additive to the second additive is 10:90 to 90:
10.
6. The nonaqueous electrolyte according to claim 1, wherein The lithium salt includes at least one selected from the group consisting of LiCl, LiBr, LiI, LiBF4, LiClO4, LiAlO4, LiAlCl4, LiPF6, LiSbF6, LiAsF6, LiB 10 Cl 10 , LiB(C2O4)2(LiBOB), LiCF3SO3, LiN(SO2F)2(LiFSI), LiCH3SO3, LiCF3CO2, LiCH3CO2 and LiN(SO2CF2CF3)2(LiBETI).
7. The nonaqueous electrolyte according to claim 1, wherein The molar concentration of the lithium salt contained in the non-aqueous electrolyte is 0.5M to 5.0M.
8. The nonaqueous electrolyte according to claim 1, wherein The organic solvent includes at least one selected from the group consisting of a cyclic carbonate organic solvent, a linear carbonate organic solvent, a linear ester organic solvent, and a cyclic ester organic solvent.
9. The nonaqueous electrolyte according to claim 1, wherein The additives also include at least one additional additive selected from the group consisting of vinylene carbonate, vinyl ethylene carbonate, fluoroethylene carbonate, propane sultone, propylene sultone, succinonitrile, adiponitrile, ethylene sulfate, lithium bis(oxalatoborate) (LiBOB), lithium difluorooxalatoborate (LiODFB), 3-trimethoxysilyl-propyl-N-aniline (TMSPa) and tris(triethylsilyl) phosphite (TMSPi).
10. A lithium secondary battery comprising: positive electrode; a negative electrode facing the positive electrode; A separator disposed between the positive electrode and the negative electrode; and The nonaqueous electrolyte according to claim 1.
Citation Information
Patent Citations
plaque stands set up for advertising purposes
CH32222A
Non-breakable filaments for bone and dental substitutes
KR1020220101642A